2008
DOI: 10.1111/j.1752-1688.2008.00220.x
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Monthly Precipitation Under Climate Change for the Upper Blue Nile River Basin, Ethiopia1

Abstract: This work develops a methodology to project the future precipitation in large river basins under limited data and climate change while preserving the historical temporal and spatial characteristics. The computationally simple and reliable conditional generation method (CGM) is presented and applied to generate reliable monthly precipitation data in the upper Blue Nile River Basin of Ethiopia where rain‐fed agriculture is prevalent. The results showed that the temporal analysis with the CGM performs better to r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
64
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(67 citation statements)
references
References 41 publications
3
64
0
Order By: Relevance
“…The dry season runs from October to January followed by a short rainy season (called "Belg") from February to May. According to Kim et al (2008), about 70% of the annual precipitation in the study area (UBN basin) is observed during the Kiremt season. The UBN basin receives up to 2,200 mm of annual rainfall.…”
Section: Site Descriptions 30mentioning
confidence: 99%
See 1 more Smart Citation
“…The dry season runs from October to January followed by a short rainy season (called "Belg") from February to May. According to Kim et al (2008), about 70% of the annual precipitation in the study area (UBN basin) is observed during the Kiremt season. The UBN basin receives up to 2,200 mm of annual rainfall.…”
Section: Site Descriptions 30mentioning
confidence: 99%
“…The UBN basin receives up to 2,200 mm of annual rainfall. The annual mean rainfall varies between 1200-1800 mm (Conway, 2000) with an increasing trend from northeast to southwest 10 (Kim et al 2008). However, the basin is characterized by large temporal fluctuations in rainfall (Conway, 2000;Taye and Willems, 2013) both in intra-annual and inter-annual scale.…”
Section: Site Descriptions 30mentioning
confidence: 99%
“…Knowledge on the relations between HBV MPs and the PCCs allows us to estimate MPs for ungauged catchment systems when the PCCs from these catchments are known. To set up a regional model for estimation of model parameters in ungauged catchments, often regression analysis are applied (see Bastola et al, 2008;Heuvelmans et al, 2006;Kim et al, 2008;Xu, 2003;Deckers et al, 2010). Such analysis is selected for this study as well.…”
Section: Establishing the Regional Modelmentioning
confidence: 99%
“…Understanding climate change and its impact on hydrological variability is important for water management, and thus has received attention from researchers in different parts of the world (e.g. Kim et al, 2008;Ma et al, 2008;Pano et al, 2010;Tekleab et al, 2013;Wang et al, 2013;Zhan et al, 2014;Zhao et al, 2015). These studies investigate how climate change, reflected in changing rainfall patterns, affects the hydrological regimes of river basins.…”
Section: Introductionmentioning
confidence: 99%